Aplikasi penggunaan urea molases multinutrient blok dan krim daun capa untuk peningkatan kesehatan ternak sapi masyarakat Gampong Blang Krueng Aceh Besar [Application of urea molasses multi nutrient block and capa leaf cream to improve cattle health in Blang Krueng Village Aceh Besar District] - Hanafiah, Muhammad; Nurliana, Nurliana; Helmi, Teuku Zahrial; Bahi, Muhammad (Buletin Pengabdian, 2024)
Blang Krueng Village has potential in the field of animal husbandry, but the livestock raised is still traditional, so that many livestock lack feed, this causes the supply of minerals to the livestock's body to decrease. Urea molasses multinutrient block (UMMB) is one of the additional feeds with a high content of nutritional supplements, especially minerals for ruminants in solid form. The purpose of the service activity is to increase community income based on the development of the ability of the farmer community by increasing the knowledge and skills of farmers regarding technology for making nutrient block and capa leaf cream to increase their cattle production. The method that used in this activity is to use the approach of community participation methods in development or Participatory Rural Appraisal (PRA). The results of this activity showed that 95% of participants are interested in practicing, developing, and transmitting their knowledge of how to make UMMB and capa leaf cream to members of farmer groups around them. The conclusion, farmers will share the knowledge that has been obtained during the service to other farmer group members as the target group of service activities.